Evaluasi Risiko Keterlambatan Pada Proyek Konstruksi Pembangkit Listrik Tenaga Uap (PLTU) Tembilahan - Riya Nisa Putri; Ari Sandhyavitri; Alfian Malik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The implementation of construction projects often mismatch between the planning schedule and the realization at site like Coal Fired Steam Power Plant Project (PLTU) in Tembilahan which is 186 days delay (209 days plan but realization in 395 days). This resulted in the overdue of the Tembilahan power plant to operate, but by the implementation of Risk Analysis, Risk Mitigation and Control obtained the following results: for 80% probability there was a decrease in the implementation time delay to 32 days. Implementation of risk management can control project risk systematically.Keywords: Risk Analysis,Delay, Project, Probability